Unveiling Research Trends in Good Governance - Fadhilah, Hasna Azmi; Rahmi, Haifa Zulfani (Department Library of Governance Institut of Home Affairs, 2023)
Background: The provision of public services by governmental entities embodies their dedication to enhancing societal well-being. The manifestation of superior and high-caliber public services serves as an inherent manifestation of effective governance. Nonetheless, there persists a deficiency in comprehensive comprehension regarding the intricacies of sound governance practices. Purpose: The objective of this study was to ascertain the prevailing research patterns within the domain of good governance. Method: To bridge this scholarly void, the investigation adopted a quantitative research paradigm incorporating a bibliometric framework to discern the trajectory of developments in the realm of good governance. Employing a purposive sampling technique, data collection centered on article documents pertaining to the specified timeframe of 2012 to 2022, encompassing works containing the designated keywords